1997
DOI: 10.1111/j.1399-6576.1997.tb04645.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of ventricular fibrillation during anaesthesia in an anaesthesia simulator

Abstract: There was very little consistency among the teams regarding treatment for VF according to accepted algorithms. An anaesthesia simulator could be a tool for training and it is a safe way of demonstrating for the anaesthetist that certain treatment algorithms and behaviour during critical incidents are the most effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…A number of assessment tools have been used to assess anaesthetists during simulations. These include time to solve the problem [2], adherence to established protocols [3], scoring systems [4] and measurement of mental workload [5]. However, proper validation of these tests and assessment tools has started only recently [6,7].…”
mentioning
confidence: 99%
“…A number of assessment tools have been used to assess anaesthetists during simulations. These include time to solve the problem [2], adherence to established protocols [3], scoring systems [4] and measurement of mental workload [5]. However, proper validation of these tests and assessment tools has started only recently [6,7].…”
mentioning
confidence: 99%
“…Leadership, team management, contingency planning, and skilled resource allocation are all key components in the optimal management of high-risk situations (Gaba et al 1994;Lighthall et al 2004). Reports within the medical literature suggest that in spite of successful completion of a course, members of teams responding to cardiac arrests do not possess essential communication skills and are likely to fail while performing vital tasks (Lindekaer et al 1997;McQuillan et al 1998;Nadel et al 2000;Iriola et al 2002). With this in mind we chose to move beyond the traditional focus of simply defining treatment goals and concentrate rather on the process required how to best accomplish these goals.…”
Section: Faculty Of Health Sciences: Team Based Cardiac Life Supportmentioning
confidence: 97%
“…Based on the literature, this is needed. Several studies have shown that guidelines for advanced life support are not followed (5,6), and focus group interviews with junior physicians have made it clear that they feel incompetent as team leaders (Lippert et al, abstract at the ASA Annual Meeting, San Francisco, CA, 2000). The qualifications needed for the anesthesiologists in this situation are theoretical knowledge and the consistent use of algorithms (medical expertise), manual skills and team performance skills (such as communication, leadership, cooperation, and the distribution of workload).…”
Section: Why Use Simulation?mentioning
confidence: 97%